Compact gesture recognition algorithm using tiny machine learning - Li, Junying (Nanyang Technological University, 2023)
For gesture recognition based on convolution neural network, general processors are not efficient for CNN implementation and cannot meet performance requirements. Plenty of great works on implementing the convolution neural network on FPGA have been carried out in recent years. But it is still a very difficult task due to the complex computation of convolution, limited hardware resources, and high-speed requirements.